Shape/temperature memory phenomena in un-crosslinked poly-ɛ-caprolactone (PCL). (November 2015) - Salvekar, Abhijit Vijay; Zhou, Ye; Huang, Wei Min; Wong, Yee Shan; Venkatraman, Subbu S.; Shen, Zexiang; Zhu, Guangming; Cui, Hai Po
Graphical abstract: Highlights: The shape/temperature memory phenomena in unmodified thermoplastic poly-ɛ-caprolactone were investigated. Effects of factors, such as, deformation method/temperature, sample size, and heating method, were evaluated. The underlying mechanism for the shape memory effect is proposed. Abstract: The shape/temperature memory phenomena based on melting in unmodified thermoplastic poly-ɛ-caprolactone (PCL) (i.e., without chemical-cross-linking) were investigated systematically. Effects of factors, such as, deformation method (uniaxial tension/compression, indentation), deformation temperature, sample size, and heating method, on the shape memory effect were evaluated. Based on these results, the underlying mechanism for the shape memory effect in chemically un-crosslinked PCL (based on melting) is proposed.